3D printed object's strength-to-weight ratio analysis for M3 liquid material. Issue 2 (3rd April 2022) - Lalegani Dezaki, Mohammadreza; Ariffin, Mohd Khairol Anuar Mohd; Appalanaidoo, Diniesh; Wahid, Zaliha; Rage, Abdullahi Musse
ABSTRACT: 3D printing processes have been used in different applications. Complex products are fabricated without tooling faster compared to conventional processes. Many ways have been proposed to evaluate the strength and stiffness of plastics, for example, tensile tests, fatigue behaviour, and crack propagation. Finite element analysis (FEA) is a way to evaluate the sample's strength in various situations. This paper investigated the capability of the Polyjet process and features' effects on a product's strength. It was found that complex parts with high accuracy and good mechanical properties were achievable by using liquid as a base material in the Polyjet process. Porous cubes were analysed to identify the influence of features, e.g. fillets, holes, and curves on mechanical properties. VisiJet M3 liquid material was used in this research, and a comparison was obtained between computer-aided engineering (CAE) simulation and laboratory experiment. Compression tests were conducted on porous cubes, and the results showed that the strength-to-weight ratio difference between simulation and experimental processes was 7.5%. The samples showed different behaviours under compression tests due to the different geometric dimensions. Thus, there was a correlation between weight and strength conducted by design optimisation, where maximum strength was achieved when the product weighed the least.